Digital transformation and institutional theory - Gegenhuber, Thomas; Logue, Danielle M., 1979-; Hinings, C. R.; Barrett, Michael I. (Emerald Publishing Limited, 2022)
This volume contains two Open Access chapters. Digital transformation is permeating all domains of business and society. Digital Transformation and Institutional Theory explores how manifestations of digital transformation requires rethinking of our understanding and theorization of institutional processes. Showcasing a collaborative forum of organization and management theory scholars and information systems researchers, the authors enrich institutional theory approaches in understanding digital transformation. Advancing institutional perspectives with an agenda for future research and methodological reflections, the chapters delve into digital transformations in relation to institutional logics and technological affordances, professional projects and new institutional agents, institutional infrastructure, and field governance. This volume deepens our understanding of the pervasive and increasingly important relationship between technology and institutions and the response of existing professions to the emergence of digital technologies. Moreover, the authors offer a cutting-edge analysis of how new digital organizational forms affect institutional fields, their infrastructure, and thus their governance.
Keywords: Organizational change -- Management.; Business -- Technological innovations.; Organizational behavior.; Business & Economics -- Management.; Management & management techniques.; elektronické knihy; electronic books